HarvestChoice: Supporting strategic investment choices in agricultural technology development and adoption - Koo, Jawoo; Pardey, Philip G. (International Food Policy Research Institute, 2020)
HarvestChoice began in 2006, when detailed and readily accessible data on agriculture, human welfare, and the environment were scarce for Africa South of the Sahara (SSA). Statistics to support agricultural policy and investment decisions in the region were often too coarse—available only at national scale. Since then, technology advances (e.g., remote sensing, geographic information systems, and modeling tools) have enabled rapid data generation.